2021
DOI: 10.1016/j.sjbs.2020.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering genetic diversity analysis of saffron (Crocus sativus L.) using RAPD and ISSR markers

Abstract: The existence of genetic diversity in Crocus sativus has globally remained a mystery till date. The study investigated PCR based DNA amplification profile of saffron using ISSR and RAPD based primers. A total of 38 amplicons were generated by ISSR primers in the range from 7 to 12 with an average of 9.50 bands per primer. 20 bands were found to be polymorphic and 18 were monomorphic with an average percentage of polymorphism as 52.48%. RAPD based amplification revealed a total 161 amplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…However, there are variations in the phenotypic and biochemical characteristics such as the percentage of various metabolites (crocin, picocrocin, and saffranal) reported from different geographical locations (Othman et al, 2020). However, there are no authentic molecular markers that can identify these variations till date (Alavi-Kia et al, 2008;Keify and Beiki, 2012;Mir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are variations in the phenotypic and biochemical characteristics such as the percentage of various metabolites (crocin, picocrocin, and saffranal) reported from different geographical locations (Othman et al, 2020). However, there are no authentic molecular markers that can identify these variations till date (Alavi-Kia et al, 2008;Keify and Beiki, 2012;Mir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…has not been done There are contradictory results on the detection of polymorphisms using marker-based analysis Some studies conclude that saffron is a monomorphic species and whole genome sequencing is needed to discriminate between its isolates Some studies show that molecular markers are quite efficient in detecting polymorphism. Such studies conclude that saffron is not monomorphic and that there is diversity which could be useful for breeding purposes AFLP analysis using methylation-sensitive restriction enzyme-sequencing (MRE-seq) has shown that phenotypically different but genetically similar accessions vary in the methylation pattern of genomic regions encoding transcription factors and may result in alternative phenotypes Epigenetic structure in saffron is highly stable and may play a vital role in the constancy of saffron phenotype variability ISSR primers are reported to be capable of easily distinguishing genuine saffron from fake one [ 44 , 47 , 47 , 48 , 51 , 52 , 54 , 88 – 91 ] 2. Transcriptomics De novo transcriptome assemblies have been created from leaves, stamens, corm, tepals, and stigmas of Crocus sativus The most valued compounds of C. sativus are synthesised inside stigma in a developmental stage-specific manner During the transition from yellow stage to red stage stigmas there is an accumulation of zeaxanthin accompanied by sharp increase in the expression of phytoene synthase, phytoene desaturase, lycopene β cyclase, β carotene hydroxylase and zeaxanthin cleavage dioxygenase CsCCD2 (carotenoid cleavage dioxygenase) ESTs are prominent in the saffron stigma libraries obtained from early stages of stigma development UDP-glucosyltransferase is vital for conversion of crocetin to crocin, and therefore causes difference in metabolite accumulation between Crocus species 1 Deoxyxylulose 5 phosphate synthase (DXS) plays a vital role in apocarotenoid accumulation in stigma There is no direct concordance in the expression of Cs AP3 and Cs NAP gene expression in saffron Identification, isolation, and biochemical characterisation of uridine diphosphate glycosyltransferase (UGT709G1), which catalyses the HTCC glucosyltransferase reaction to yield picrocrocin, can provide a vital lead for the industrial production of picrocrocin/safranal Differentially expressed full-length transcripts of flowering and non-flowering saffron crocus have been identified and characterised Stigma development in field- and indoor-cultivated saffron is similar with respect to apocarotenoid content and gene expression profiles of 12 genes involved in apocarotenoid biosynthesis Carotenoid cleavage dioxygenase (CCD2) catalyzes the first step of crocin biosynthesis from carotenoid zeaxanthin and gets expressed at an extremely high level in the stigma as compared to corm, leaf, tepal, and stamen A C-class floral homeotic gene AGAMOUS (CsAG) gene is vital for stigma development of saffron.…”
Section: Saffron Growth Development and Diseasementioning
confidence: 99%
“…Some efforts have been made to improve our understanding of the genomic organisation of Crocus species. These studies are mostly based on RAPD [47], [48], Mir, Mansoor [49], IRAP markers [50,51], Nuclear gene diversity [52][53][54], AFLP and SSR [55].…”
Section: Diversity Of Saffron and Its Characterizationmentioning
confidence: 99%